AFM and SEM-FEG study on fundamental mechanisms leading to fatigue crack initiation. (July 2015) - Man, J.; Valtr, M.; Petrenec, M.; Dluhoš, J.; Kuběna, I.; Obrtlík, K.; Polák, J.
Abstract: Early stages of surface relief evolution of persistent slip markings (PSMs) in polycrystalline 316L austenitic stainless steel cycled with constant plastic strain amplitude at 93, 173 and 573 K were studied using atomic force microscopy (AFM) and high-resolution scanning electron microscopy (SEM-FEG). Qualitative and quantitative data on the morphology of PSMs, occurrence of extrusions and intrusions and the kinetics of extrusion growth are reported for all temperatures. PSMs start in all cases as surface extrusions which are later accompanied by formation of intrusions. This finding is discussed with respect to the point defect formation within areas of localized cyclic slip and primarily to their mobility at different temperatures. Consequences of migration of respective point defects for surface relief formation and the conditions for creation of fatigue crack embryos, i.e. sharp intrusions are highlighted.